Tibial tubercle osteotomy (Fulkerson procedure) on women athlete with anterior knee pain: a case series - Mustamsir, Edi; Isnansyah, Yun (International Journal of Research in Medical Sciences, 2021)
Anterior knee pain (AKP) is one of the most frequent complaints in knee conditions of adolescent and young adult patients. Tibial tuberosity osteotomy (Fulkerson procedure) is a well-described treatment option for a broad range of patellofemoral joint disorders. This study aimed to evaluate the clinical outcomes of tibial tubercle osteotomy and prognostic factors correlated with the outcomes in adolescents’ athletes affected by anterior knee pain. Three patients treated with tibial tubercle osteotomy for anterior knee pain were prospectively evaluated using the Anterior Knee Pain Scale (AKPS), The Western Ontario and McMaster Universities Arthritis Index (WOMAC) and the part of the International Knee Documentation Committee (IKDC) score to find different potential risk factors as an objective evaluation. The three cases are showing improvement in overall scores, both in six months (WOMAC 72.4; KUJALA 64.6%; IKDC 52.1%) and after one year (WOMAC 82.6; KUJALA 83.3%; IKDC 70.3%) following the surgical procedure. Patient 1 and patient 2 obeyed the physiotherapy schedules and checked their condition regularly. Their scores indicate an immense improvement than patient 3, who did not comply with the physiotherapy nor the check-up. However, the comparison analysis shows a significant increase of the scores for all three assessment methods (WOMAC, KUJALA and IKDC), that implies a good result of clinical outcome may still be achieved even without a close follow up. Even though the Fulkerson procedure was the treatment option for a broad range of AKP, a different comprehensive range result of the scores was found.